Chromosome 15q BP4-BP5 Deletion in a Girl with Nocturnal Frontal Lobe Epilepsy, Migraine, Circumscribed Hypertrichosis, and Language Impairment - Pavone, Piero; Pappalardo, Xena Giada; Nelly Ohazuruike, Ugochi Ngaobiri; Striano, Pasquale; Parisi, Pasquale; Corsello, Giovanni; Marino, Simona Domenica; Ruggieri, Martino; Parano, Enrico; Falsaperla, Raffaele (Journal of epilepsy research, 2020)
The 15q13.3 microdeletion (microdel15q13.3) syndrome (OMIM 612001) has been reported in healthy subjects as well as in individuals with a wide spectrum of clinical manifestations ranging from mild to severe neurological disorders, including developmental delay/intellectual disability, autism spectrum disorder, schizophrenia, epilepsy, behavioral problems and speech dysfunction. This study explored the link between this genomic rearrangement and nocturnal frontal lobe epilepsy (NFLE), which could improve the clinical interpretation. A clinical and genomic investigation was carried out on an 8-year-girl with a deletion flanking the breakpoints (BPs) 4 and 5 of 15q13.3 detected by array comparative genomic hybridization analysis, affected by NFLE, migraine with aura, minor facial features, mild cognitive and language impairment, and circumscribed hypertrichosis. Literature survey of clinical studies was included. Nine years follow-up have displayed a benign course of the epileptic disorder with a progressive reduction and disappearance of the epileptic seizures, mild improvement of cognitive and language skills, partial cutaneous hypertrichosis regression, but stable ongoing of migraine episodes. A likely relationship between the BP4-BP5 deletion and NFLE with other symptoms presented by the girl is discussed together with a review of the literature on phenotypic features in microdel15q13.3.